2015
DOI: 10.1039/c4ra15376f
|View full text |Cite
|
Sign up to set email alerts
|

UV-A and UV-B excitation region broadened novel green color-emitting CaGd2ZnO5:Tb3+ nanophosphors

Abstract: CaGd2ZnO5:Tb3+ nanophosphors showed the broadened excitation region as compared to Y2O3:Tb3+ and Gd2O3:Tb3+ phosphors, which covered almost the entire UV-B and UV-A regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The PLE spectra of Dy 3 þ ions consisted of a strong excitation band from 200 to 250 nm with the maxima at 230 nm. This band can be ascribed to the host absorption band (HAB) which is similar to our earlier report on the CGZO:Tb 3 þ nanophosphor [16]. The spectra also contained some weak excitation peaks at 275 and 312 nm corresponding to the electronic transitions ( 8 S 7/2 -6 11/2 ) and ( 8 S 7/2 -6 P 7/2 ) of Gd 3 þ ions, transitions of the Gd 3 þ ions decreased gradually by increasing the Dy 3 þ ion concentration.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The PLE spectra of Dy 3 þ ions consisted of a strong excitation band from 200 to 250 nm with the maxima at 230 nm. This band can be ascribed to the host absorption band (HAB) which is similar to our earlier report on the CGZO:Tb 3 þ nanophosphor [16]. The spectra also contained some weak excitation peaks at 275 and 312 nm corresponding to the electronic transitions ( 8 S 7/2 -6 11/2 ) and ( 8 S 7/2 -6 P 7/2 ) of Gd 3 þ ions, transitions of the Gd 3 þ ions decreased gradually by increasing the Dy 3 þ ion concentration.…”
Section: Resultssupporting
confidence: 89%
“…1(a) shows the XRD patterns of the CGZO:1Dy 3 þ nanophosphor annealed at 1200 ºC. According to our earlier reports [15,16], the optimal annealing temperature was found to be at 1200 ºC and the dilute concentrations of doping ions did not show any considerable effect on the crystallite size and phase purity [16]. Recently, Xu et al [17] reported the crystal structure of the novel CGZO host lattice, but the JCPDS card is not available till now.…”
Section: Resultsmentioning
confidence: 96%
“…17 The lighting and photonic sectors progressively view nano-phosphors as an intriguing future among the numerous nanoparticles that are now accessible. 18 The photoluminescence (PL) properties of nanoscale materials have z E-mail: hrasool23@gmail.com received significant attention in the past decade owing to their optical characteristics and photoluminescence outcomes from the de-excitation of the excited electron to the ground state. Investigators have previously reported several industrial important nano-phosphors and regarded them as prospective because of their potential use in numerous highly effective and novel displays and devices.…”
Section: Progress Of the Nanophosphorsmentioning
confidence: 99%
“…The occurrence of low phonon frequency and minimal amounts of Tb 3+ in the host structure will inhibit multiphonon relaxation and cross‐relaxation among Tb 3+ ions, leading to noticeable blue emissions from Tb 3+ . As a result, selecting an appropriate host structure and optimal Tb 3+ concentrations allows the production of different emission colors in Tb 3+ ‐doped phosphors 14–25 …”
Section: Introductionmentioning
confidence: 99%